PERAN KEBIJAKAN DIVIDEN DALAM MEMEDIASI PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Yuphi Handoko; Devi Ratna Ningsih; Sugeng Priyanto (LPPM Politeknik Pratama, 2024)
This study aims determine the effect of Liquidity and Profitability on Firm Value with Dividend Policy as an Intervening variable in food and beverage sub sector manufacturing companies listend on the Indonesia Stock Exchange for the period 2017 – 2022. The sample of this research is 10 food and beverage sub sector companies listed on the Indonesia stock exchange for the 2017-2022 period. In this study, path analysiswas carried out using SPSS version 25 program and Microsoft Excel 2019. The results showed that 1) Liquidity has no significant effect on Dividend Policy 2) Profitability has a significant effect on Dividend Policy 3) Dividend Policy has no effect on Firm Value 4) Liquidity has a significant negative effect on Firm Value 5) Profitability has a significant effect on Firm Value 6) Dividend Policy is able to mediate the effect of Liquidity on Firm Value 7) Dividend Policy is unable to mediate the effect of Profitability on Firm Value.